Laparoscopy-assisted uterovaginal anastomosis in a patient with atypical cervicovaginal malformation: a case report - Naem, Antoine; Moufawad, Graziella; Sultan, Suzana; Sleiman, Zaki (Frontiers in Medicine, 2025)
Cervicovaginal anomalies are rare and form 4–7% of the Müllerian anomalies. Traditionally, cervicovaginal agenesis/dysgenesis had been treated by hysterectomy due to the high risks of restenosis and sepsis which are associated with cervical canalization. In this work, we report the case of a 14-year-old patient who presented with amenorrhea and cyclic abdominal pain. The patient had normal secondary sexual development. Magnetic resonance imaging revealed hematometra and bilateral hematosalpinx. Laparoscopic exploration identified an obstructed cervix and blunt vagina. The patient underwent direct cervicovaginal anastomosis under laparoscopic guidance. After 1 month of follow-up, the patient had normal menstruation and a healthy uterine cavity and cervical canal upon hysteroscopy.